Using Karuta Game to Enhance Vocabulary Mastery of Elementary School Students in Sidomulyo of Sibiru Biru Sub-District - Tarigan, Bahagia; Hati, Lila Pelita (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Vocabulary learning plays an important role in learning English, especially in elementary schools which emphasize English learning on vocabulary mastery. However, vocabulary learning often makes elementary school students feel bored because they are assigned to memorize as many English words as possible while they sometimes do not understand the meaning of the words. Therefore, teachers should find several possible techniques that can attract students’ attention and bring out their motivation, one of which is using games, such as the karuta game. This paper aims at describing how the karuta game is implemented in teaching vocabulary and how it enhances the elementary school students’ vocabulary mastery. This is a descriptive study taking the elementary school students living in Sidomulyo of Sibiru Biru Sub-District, Deli Serdang Regency, North Sumatra, as the participants. The data were collected using observations and interviews and were analyzed qualitatively. The results show that (i) the karuta game is easy to use because it does not have a complicated rule; furthermore, it is flexible because it can be modified in several ways following the vocabulary intended to introduce; (ii) the karuta game benefits the students in bringing up their motivation in learning English vocabulary, providing them a comprehensive conceptual meaning of each vocabulary, and improving their pronunciation. It is concluded that the karuta game is a good technique in enhancing elementary school students’ vocabulary mastery.